The Latin American forage seed market: Developments, trends, and future opportunities - Gallo Caro, Irieleth; Enciso, Karen; Díaz, Manuel Francisco; Burkart, Stefan (Bioversity International and the International Center for Tropical Agriculture, 2021)
Because of global population growth, increased purchasing power, environmental degradation, and a growing demand for meat, cattle farming faces many challenges regarding the promotion of approaches to sustainable intensification. As a part of satisfying this demand, environmental restrictions must be considered, making it necessary to intensify production systems through the development and adoption of innovative technologies that allow increasing efficiency and productivity while decreasing the use of land and other resources. The transformation of the cattle sector not only has future implications but also economic, social, and cultural connotations in the present. The Latin American cattle sector contributes with approximately 30% of the global beef trade and 46% of the agricultural gross domestic product (GDP) of the region. It also employs a significant part of the rural population and 80% of the producers in the region are smallholder farmers (FAO, 2016). All these attributes can be understood as important for the achievement of the Sustainable Development Goals (SDGs).